2015
DOI: 10.1002/2015rs005772
|View full text |Cite
|
Sign up to set email alerts
|

Antenna gain and link budget for waves carrying orbital angular momentum

Abstract: This paper addresses the RF link budget of a communication system using unusual waves carrying an orbital angular momentum (OAM) in order to clearly analyze the fundamental changes for telecommunication applications. The study is based on a typical configuration using circular array antennas to transmit and receive OAM waves. For any value of the OAM mode order, an original asymptotic formulation of the link budget is proposed in which equivalent antenna gains and free-space losses appear. The formulations are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…tends to straight lines of slope −20jlj dB/decade. It is consistent with an attenuation of 1 D 2jlj , which has already been proved in [21,22]. Consequently, it would be concluded that for the wave with OAM mode of l propagating in free space, one should observe the approximately linear jlj-scaling of the wave divergence in the far-field.…”
Section: Mathematical Model and Propagation Characteristics Of A Circsupporting
confidence: 84%
“…tends to straight lines of slope −20jlj dB/decade. It is consistent with an attenuation of 1 D 2jlj , which has already been proved in [21,22]. Consequently, it would be concluded that for the wave with OAM mode of l propagating in free space, one should observe the approximately linear jlj-scaling of the wave divergence in the far-field.…”
Section: Mathematical Model and Propagation Characteristics Of A Circsupporting
confidence: 84%
“…This number is identical to the one given by formula (26) (19) which also provides an a-posteriori check of (16). Of course, all these considerations go against the pretension [2], [9], [11] of arbitrarily enlarging the channel capacity.…”
Section: Va the Forward Problem: Singular Values And Singular Functimentioning
confidence: 71%
“…Concerning the value of R, we limited the analysis to distances not much larger than the Fraunhofer value RF=8a1 2 /λ. This choice has been induced by the circumstance that the OAM antennas' performance in terms of ratio between received and transmitted powers decays as R -2(|ℓ|+1) {see (20) in [16], and also [7], [8], [10], [12]}. For each combination of ℓ, a1=a2, Nℓ, and R, in order to evaluate the energy necessary to generate a particular vortex order, the achieved PAP value has been compared with that pertaining to the zero-order field (let us say PAP0).…”
Section: Va the Forward Problem: Singular Values And Singular Functimentioning
confidence: 99%
“…In other words, at the same location, the received power of signals carrying different OAM mode number will be different, which makes it more difficult to multiplex beams of different OAM modes. Thus, the above disadvantages existing in OAM antenna have severely restricted its practical application in wireless communication systems [19], [20].…”
Section: Introductionmentioning
confidence: 99%